2021
DOI: 10.1177/2325967120967125
|View full text |Cite
|
Sign up to set email alerts
|

Operative Treatment of Bipartite Patella in Pediatric and Adolescent Athletes: A Retrospective Comparison With a Nonoperatively Treated Cohort

Abstract: Background: Bipartite patella (BPP) is a developmental anomaly that forms when incomplete patellar ossification leaves a residual fibrocartilaginous synchondrosis between ossification centers. Repetitive traction forces across the synchondrosis can cause knee pain, most commonly presenting in adolescence. Symptoms frequently resolve with nonoperative management. Few surgical case series exist to guide treatment approaches for refractory pain. Purpose: To investigate the clinical features, surgical techniques, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…When conservative treatment fails, surgery can then be considered [ 9 ]. Few studies have reported on the outcomes of operative treatment in the adult population [ 5 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…When conservative treatment fails, surgery can then be considered [ 9 ]. Few studies have reported on the outcomes of operative treatment in the adult population [ 5 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…For those who fail conservative management, surgical excision with soft tissue repair and/or release can be performed. 5,41,42…”
Section: Partite Patellamentioning
confidence: 99%